Accelerometer‐Measured Sedentary Patterns are Associated with Incident Falls in Older Women. Issue 3 (30th November 2020) - Rosenberg, Dori E.; Rillamas‐Sun, Eileen; Bellettiere, John; LaMonte, Michael; Buchner, David M.; Di, Chongzhi; Hunt, Julie; Marshall, Stephen; Stefanick, Marcia; Zhang, Yuzheng; LaCroix, Andrea Z.
Abstract : Background/Objective: Falls cause significant problems for older adults. Sedentary time is associated with lower physical function and could increase the risk for falls. Design: Prospective study. Setting: Sites across the United States. Participants: Older women (N = 5, 545, mean age 79 years) from the Women's Health Initiative Objective Physical Activity and Cardiovascular Health study. Measurements: Accelerometers worn at the hip for up to 1 week collected measures of daily sedentary time and the mean sedentary bout duration, a commonly used metric for sedentary accumulation patterns. For up to 13 months after accelerometer wear, women reported daily whether they had fallen on monthly calendars. Results: In fully adjusted models, the incident rate ratios (95% confidence interval) for quartiles 1 (lowest), 2, 3, and 4 of sedentary time respectively were 1.0 (ref.), 1.07 (0.93–1.24), 1.07 (0.91–1.25), and 1.14 (0.96–1.35; P ‐trend = .65) and for mean sedentary bout duration was 1.0 (ref.), 1.05 (0.92–1.21), 1.02 (0.88–1.17), and 1.17 (1.01–1.37; P ‐trend = .01), respectively. Women with a history of two or more falls had stronger associations between sedentary time and falls incidence compared with women with a history of no or one fall ( P for interaction = .046). Conclusions: Older women in the highest quartile of mean sedentary bout duration had a significantly increased risk of falling. Women with a history of frequent falling may be at higher risk for falling if they have high sedentary time. Interventions testing whether shortening total sedentary time and/or sedentary bouts lowers fall risk are needed to confirm these observational findings.